POTENSI IKAN LELE (CLARIAS GARIEPINUS) DAN LABU KUNING (CUCURBITA MOSCHATA) SEBAGAI FORMULA ENTERAL DIABETES MELLITUS - Hartati, Yuli; Erian, Chika; Telisa, Imelda; Meilina, Ayu; Podojoyo, Podojoyo; Faridi, Ahmad (UHAMKA PRESS, 2023)
Diabetes Mellitus is a non-communicable disease whose incidence rate is still quite high in Indonesia. Currently, the availability of enteral diabetes mellitus formulas derived from local food is still small. Meanwhile, the price of commercial enteral formula is quite expensive. Whereas local food has the potential as anti-diabetic and anti-hyperglycemia. Pumpkin and catfish are local food ingredients that have the potential to be alternative enteral formulas for people with diabetes mellitus. Yellow pumpkin contains antioxidants that play a role in reducing blood sugar. Catfish as a source of energy and protein needed by diabetes mellitus patients. The purpose of this study was to determine the acceptability of enteral diabetes mellitus formula based on pumpkin flour and catfish meal. This study used a quasi-experimental, with a non-factorial Completely Randomized Design (CRD) trial design by making 3 diabetes mellitus formulas. The acceptability of the three formulations obtained an average ranking score in Formula 1 of 2.32, Formula 2 of 1.73, and Formula 3 of 1.93. The results of the proximate analysis of Formula 1 had carbohydrate content of 64.85%, protein of 16.50%, dietary fiber of 4.69%, ash of 4.32%, water 4.53%, total energy 413.60 kcal/100g, energy from fat 88.20 kcal/100g and total fat content 9.80%. Enteral formula based on pumpkin and catfish flour has the potential as enteral food for Diabetes Mellitus patient.